The Choice of Foreign Market Entry Modes: The Role of Resources and Industrial Driving Forces - Andrea S. Gubik; Sándor Karajz (Entrepreneurial Business and Economics Review, 2014)
The objective of the paper is to analyse the effects of corporate resources, attitudes of owner/entrepreneur/manager to internationalisation and the characteristics of the business industry on the entry mode choice.